LEGAL PROVISION OF PUBLIC SERVICES IN THE REPUBLIC OF KAZAKHSTAN AND EUROPEAN COUNTRIES: A COMPARATIVE EXPERIENCE - Zhanuzakova, Лейла Тельмановна; Aubakirova, Индира Ураловна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article discusses the experience of European countries to establish a legal framework, the development of standards and regulations of public services, the implementation of control mechanism for the quality of their provision, development of information technologies for the provision of public services, to ensure the participation of citizens in the development of standards and monitoring the quality of public services.